DUKUNGAN LINTAS SEKTOR DALAM MENINGKATKAN GERAKAN MASYARAKAT HIDUP SEHAT - Sunandar, Kuslan; Hatimah, Ihat; Suryadi, Ace; Shantini, Yanti (Poltekkes Kemenkes Bandung, 2024)
The prevalence of non-communicable diseases in Indonesia showed a significant increasing trend, from 25% at the end of 2013 to 35% at the end of 2018. Prevention efforts in a community had to be conducted through healthy lifestyle implementation characterized by four indicators, namely physical activity, daily fruit and vegetable intake, not smoking, and routine health checks. Public awareness of healthy life is shallow, even though they have a high educational background. The research aimed to know the role of cross-sector support programs as a solution in improving the Healthy Life Behavior of the citizen. This research was conducted in July-August 2018 in 22 working areas of the Bandung City Health Center. The research used a cross-sectional approach design. The respondents were 205 people, using the purposive random sampling technique. The analysis used chi-square test. The results showed that respondents had poor knowledge about GERMAS, 60.4% of whom were also bad at implementing GERMAS. The respondents whose attitude towards GERMAS was poor, 61.0% of them were also poor in implementing GERMAS. Most people had not felt cross-sector support. There was a significant relationship between cross-sector support and the improvement of people's healthy clean living behavior. The research concluded that almost all people have good knowledge and attitudes about GERMAS, but most people were not good at implementing GERMAS, and there were most people who do not feel any cross-sectoral support in implementing GERMAS. There was a meaningful relationship between cross-sectoral support, both government and private, and the implementation of GERMAS.